Dynamics of surface alloying promoted by cadmium underpotential deposition-anodic stripping cycles on irregular silver electrodeposits - Martins, M. E. (1994)
The underpotential deposition of Cd from dilute aqueous 5 × 10−3 M CdSO4 + 0.5 M Na2SO4 + 0.01 M H2SO4 on Ag electrodeposits grown on polyfaceted Pt single-crystal microspheres was studied using potentiodynamic and potentiostatic techniques, transmission electron diffraction, scanning tunneling microscopy and X-ray photoelectron spectroscopy. Ag electrodeposits were grown in 5 × 10−3 M Ag2SO4 + 0.5 M Na2SO4 + 0.01 M H2SO4 at cathodic overpotentials ηc of −0.06 V and −0.58 V to form a columnar and dendritic Ag surface respectively. Surface rearrangement processes involving the formation of Cd + Ag alloys were studied by stripping voltammetry after the potential was held for a certain time at different preset values covering the potential range in which the degree of surface coverage by Cd atoms was less than or close to unity (θc⩽ 1) on both Ag surfaces. Surface diffusion and penetration of Cd atoms into bulk Ag for θc⩽ 1 are discussed. A place-exchange mechanism is advanced to account for the kinetics of Cd + Ag alloy formation.